Management leading & collaborating in a competitive world - Bateman, Thomas S.; Snell, Scott (McGraw-Hill Irwin, 2015)
Bateman and Snell's Management: Leading & Collaborating in a Competitive World is a text with a fully modernized functional approach. This text is maintaining the four traditional functions of planning, organizing, leading, and controlling, while modernizing and re-visioning the concepts as delivering strategic value, building a dynamic organization, mobilizing people, and learning and changing. Bateman/Snell' results-oriented approach is a unique hallmark of this textbook. In this ever more competitive environment there are five essential types of performance, on which the organization beats, equals, or loses to the competition which are cost, quality, speed, innovation, service and sustainability. These six performance dimensions, when done well, deliver value to the customer and competitive advantage to you and your organization. Throughout the text Bateman & Snell remind students of these five dimensions and their impact on the "bottom line" with marginal icons contributing to the leadership and collaboration theme, which is the key to successful management. People working with one another, rather than against, is essential to competitive advantage.